Design and fabrication of vegetables dicer / Muhammad Luqman Nasaruddin - Nasaruddin, Muhammad Luqman (2023)
Technology-enabled automation has significantly reduced human labour and time. In our hectic lives, slicing vegetables is a risky and time consuming task. The related obstacles, such as time constraints, contamination, and so on, make the work challenging for anyone in charge. Vegetables must be chopped by hand. It still widespread at hostels and restaurants that cater to a wide range of customer tastes and preferences. The primary goal of this technology is to reduce human effort and time. The goal of this initiative is to creating a specific product called automated vegetable cutting system to solve the concerns indicated above